Asparagine Synthetase Gene OsASN2 Is Crucial for Rice Seed Development and Germination - Rui Hu; Kaiming Liang; Xiangyu Hu; Meijuan Li; Qunhuan Ye; Yuanhong Yin; Cai Tang; Xinyu Wang; Youqiang Fu; Junfeng Pan; Mingyong Zhang; Xuhua Zhong (Plants)
Seed development plays a critical role in determining both crop yield and grain quality in rice. As a key nutrient storage organ, the rice endosperm development not only contributes to grain filling but also plays an essential role during the early stages of seed germination. Amino acid metabolism is active during the process of seed development and seed germination. Asparagine is a primary amino acid responsible for long-distance organic nitrogen transport in plants. Asparagine synthetase catalyzes the synthesis of asparagine from aspartate and glutamine. In this study, CRISPR/Cas9-mediated knockout mutants of the OsASN2 gene of rice were generated. Homozygous mutants exhibited complete failure of seed germination, and heterozygotes could not produce homozygous offspring. Endosperm development of homozygous mutant seeds showed severe defects. Additionally, interacting protein screening combined with pull-down and co-immunoprecipitation (Co-IP) assays confirmed that OsASN2 physically interacted with pyruvate phosphate dikinase OsPPDKB, the mutants of which showed impaired endosperm development. These findings collectively indicate that OsASN2 plays a critical role in seed development and germination in rice.